Odontoblast-like cells differentiated from dental pulp stem cells retain their phenotype after subcultivation (2018)
Odontoblasts, the main cell type in teeth pulp tissue, are not cultivable and they are responsible for the first line of response after dental restauration. Studies on dental materials cytotoxicity and odontoblast cells physiology require large quantity of homogenous cells retaining most of the phenotype characteristics. Odontoblast-like cells (OLC) were differentiated from human dental pulp stem cells using differentiation medium (containing TGF-β1), and OLC expanded after trypsinization (EXP-21) were evaluated and compared. Despite a slower cell growth curve, EXP-21 cells express similarly the odontoblast markers dentinal sialophosphoprotein and dentin matrix protein-1 concomitantly with RUNX2 transcripts and low alkaline phosphatase activity as expected. Both OLC and EXP-21 cells showed similar mineral deposition activity evidenced by alizarin red and von Kossa staining. These results pointed out minor changes in phenotype of subcultured EXP-21 regarding the primarily differentiated OLC, making the subcultivation of these cells a useful strategy to obtain odontoblasts for biocompatibility or cell physiology studies in dentistry.